Notes on the marine algae of the International Biosphere Reserve Seaflower, Caribbean Colombia VIII: new records of red algae (Rhodophyta) from San Andres, Old Providence, and Saint Cataline, Colombia - Reyes-Gómez, Viviana Patricia; Velásquez Pomar, Hernán; Gavio, Brigitte (Instituto de Ecología, A.C., 2021)
Background and Aims: During the past decade, phycological research in the Seaflower International Biosphere Reserve has revealed a much more diverse marine flora than historically appreciated. This work aims to contribute to the knowledge of macroalgal biodiversity in the Archipelago of San Andres, Old Providence and Saint Cataline, Colombian Caribbean, adding 11 new records of red algae. Methods: The samples were collected around the islands in ten points covering different ecosystems, by SCUBA diving at depths between 0 and 37 m. Sampling was carried out between August and November 2009, December 2012, and September 2019 during the Seaflower Scientific Expedition. The algae collected were preserved in a 4% formalin/seawater solution. The identification was carried out using an optical microscope and specialized literature. All specimens were deposited in the herbarium JIW of the Biology Department of the Universidad Nacional de Colombia, Bogotá, Colombia. Key results: Eleven species of red macroalgae are newly reported for the Seaflower International Biosphere Reserve in the Caribbean Sea. Of these taxa, six have been previously reported for the Colombian Caribbean: Botryocladia spinulifera, Champia taironensis, Dasya caraibica, Pterocladiella bartlettii, Seirospora occidentalis, Spyridia aculeata subsp. complanata. The remaining five species are new records for the country: Botryocladia cf. bahamensis, Botryocladia cf. bermudana, Ceramium brevizonatum var. caraibicum Gloioderma iyoense and Wrightiella tumanowiczii. With these results the International Biosphere Reserve Seaflower hosts 153 species of Rhodophyta, belonging to 12 orders, 27 families and 73 genera. Conclusions: With the research carried out in the last 10 years, the number of registered taxa has increased from 202 to 325, which represents a 62% increase in the knowledge of macroalgae diversity and places the Archipelago in the second most diverse region in the Colombian Caribbean.